Method for coating a substrate with a particulate stabilized foam - Patents.com
The use of particulate stabilized foam in substrate channels addresses the challenges of precise coating depth control and backpressure reduction in emission control devices, improving catalyst activity and compliance with emissions standards.
Patent Information
- Application Number
- JP2021170061
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-04-11
- Filing Date
- 2021-10-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2037-04-10
AI Technical Summary
Existing methods for coating substrates with catalytic components in emission control devices face challenges in achieving precise control over coating depth and reducing backpressure, particularly in diesel particulate filters, due to issues with washcoat loading and soot accumulation, which affect engine performance and emissions compliance.
A method involving the use of particulate stabilized foam is introduced into the substrate channels through vacuum or pressure, allowing for precise application and reduced backpressure by forming a porous solid foam layer that enhances catalyst activity and soot recovery.
The method reduces backpressure in emission control devices, improves catalyst activity, and facilitates precise control over coating depth, thereby enhancing engine performance and compliance with stringent emissions standards.
Smart Images

Figure 0007603567000004 
Figure 0007603567000005 
Figure 0007603567000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for coating a substrate with a particulate stabilized foam, the coated substrate being used in an emission control device for treating or removing pollutants from exhaust gases produced by an internal combustion engine. The present invention further relates to an emission control device comprising a substrate and a solid foam layer, and uses of the emission control device. [Background technology]
[0002] Emission control devices for treating exhaust gases from internal combustion engines in mobile and stationary applications (e.g., catalysts such as three-way catalysts and diesel oxidation catalysts) typically include a substrate (e.g., a honeycomb monolith substrate) that is coated with a liquid that contains the catalytic components. During the coating process, problems can arise that can depend on the properties of the substrate being coated (e.g., channel size, the material the substrate is made from and its porosity) and the properties of the liquid used for coating (e.g., rheology). To address these problems, various methods and apparatus have been developed by emission control device manufacturers.
[0003] WO 2007 / 068127 describes a method for preparing wet foams exhibiting long-term stability, in which partially lyophobic colloidal particles are used to stabilize the gas-liquid interface of the foam. In one embodiment, the particles are partially lyophobicized in-situ by first treating the hydrophilic particles with amphiphilic molecules that have a specific solubility in the liquid phase of the suspension. However, WO 2007 / 068127 does not disclose or teach any coating application.
[0004] In "a novel method of coating a particle stabilized alumina foam on a porous alumina substrate", Materials Letters, 88, 40-42, 2012, Ha et al. describe a method for coating a particle stabilized alumina foam on a porous alumina substrate without using an external force to apply the foam. They used a dip-coating process that relies on capillary forces to draw the foam onto the porous alumina substrate.
[0005] The synthesis of open-cell particulate stabilized Al2O3 foams using Al(OH)3 particles has been described (see Scripta Materialia, 76, 85-88, 2014). The resulting liquid foams were then dried in Perspex before being subjected to controlled drying. TM It was molded using a mold. No external force was applied.
[0006] DE102007002903 describes a method for applying a catalytic washcoat to a substrate. The washcoat is vaporized or degassed before application. To achieve the desired gas content, the gas bubbles are stabilized or destabilized through the addition of certain additives (surfactants / defoamers). Summary of the Invention
[0007] The inventors have surprisingly discovered that coating a substrate with a particulate stabilized foam can achieve certain advantages that overcome the disadvantages of using washcoats in typical coating methods for manufacturing emission control devices. The use of particulate stabilized foam in such methods provides excellent control over the shallow dose of coating that can be applied to the substrate, and also avoids the use of more washcoats than necessary.
[0008] The present invention relates to a method for coating a substrate with a foam, the method comprising: (a) introducing foam into a substrate including a plurality of channels through open ends of the channels at a first end of the substrate; and (b) optionally applying (i) a vacuum to the open ends of the channels at the second end of the substrate, and / or (ii) pressure to the open ends of the channels at the first end of the substrate. wherein the foam comprises a particulate material and wherein the foam is a stabilized particle.
[0009] The present invention allows for the production of coated substrates having a porous solid foam layer. Such coated substrates have one or more advantages over coated substrates that have been coated using conventional washcoat methods. The coated substrates may be used as, or form part of, emission control devices.
[0010] An emission control device having a porous solid foam layer disposed on a substrate may exhibit reduced backpressure in an exhaust system as compared to an identically formulated emission control device made from a washcoat. The reduced backpressure is particularly advantageous for emission control devices that include a filtering substrate, such as a filtering honeycomb monolith substrate. The open cell structure of the solid foam layer may facilitate passage of exhaust gas through the layer, and the pores may aid in soot collection.
[0011] The porous solid foam layer typically has a high specific surface area compared to a layer of the same composition produced by a conventional washcoating process, which can result in improved activity of the emission control device.
[0012] The porous solid foam layer has a rough surface that can provide good contact between components of the solid foam layer (e.g., catalytic materials) and soot trapped from the exhaust gas on the solid foam layer. This surface roughness can promote oxidation of the soot, such as when NO2 or O2 are used as the oxidizer.
[0013] The present invention further relates to a solid foam layer, the solid foam layer being obtained or obtainable by the method of the present invention.
[0014] The present invention provides an emission control device for treating or removing pollutants from exhaust gases produced by an internal combustion engine. The emission control device includes a solid foam layer disposed or supported on a substrate, which is obtained or obtainable from a method for coating a substrate with a foam of the present invention. Additionally or alternatively, the emission control device includes a substrate and a solid foam layer having an open cell structure, where the solid foam layer is disposed or supported on the substrate. The substrate typically includes a plurality of channels.
[0015] The present invention also relates to an exhaust system for treating or removing pollutants from exhaust gases produced by an internal combustion engine, the exhaust system comprising an emission control device according to the present invention.
[0016] Further aspects of the invention relate to methods and uses of emission control devices.
[0017] A first method aspect of the present invention is a method for treating or removing pollutants from exhaust gases produced by an internal combustion engine. The method includes passing exhaust gases produced by the internal combustion engine through an emission control device according to the present invention. The method may also be a method of avoiding back pressure build-up in an exhaust system of the internal combustion engine.
[0018] A first mode of use of the present invention relates to the use of an emissions control device in the exhaust system of an internal combustion engine to avoid the build-up of back pressure within the exhaust system.
[0019] In a first method and use embodiment, the substrate (ie, the substrate of the emission control device that includes the solid foam layer) is a filter substrate, such as a filtering honeycomb monolith substrate.
[0020] Backpressure is an important characteristic of automotive catalysts. An increase in backpressure can cause the engine to do additional mechanical work and / or less energy to be extracted when exhaust turbines are used. This can result in higher fuel consumption, increased particulate matter and CO emissions, and higher exhaust temperatures. Emission standards, i.e. the amount of pollutants allowed to be emitted from a vehicle, e.g. Euro 5 and Euro 6, are becoming more stringent and also include legal requirements for in-use OBD verification of continued catalyst effectiveness. OBD requirements are particularly relevant for catalyzed filters, since vehicle manufacturers typically include in their vehicle designs periodic active removal of particulate matter retained in the filter to maintain efficient engine performance, where exhaust gas temperature is increased using e.g. fuel injection engine management, and / or fuel is injected into the exhaust gas downstream of the engine and burned over a suitable catalyst. As vehicle manufacturers demand catalyst products that are durable for the entire (vehicle) life, manufacturers of catalyzed filters try to hinder catalyst deactivation over time by loading as much catalyst as possible into the filter.
[0021] Engine exhaust backpressure can cause many problems in modern engines, especially diesel engines equipped with complex aftertreatment systems, and especially diesel engines that have a diesel particulate filter (DPF). The main cause of increased backpressure is soot buildup in the diesel particulate filter. If the diesel particulate filter is not regenerated periodically, the increased backpressure will occur as described above, causing a number of problems.
[0022] Concerns over problems with increased backpressure also impact the design of emission control devices, which must consider the effect that washcoat loading may have on backpressure. Increased washcoat loading can affect exhaust gas flow through the filter walls by increasing resistance before the exhaust gas reaches the walls. Additionally, washcoats can be located within the filter pores, further reducing exhaust gas flow. Soot buildup within the filter walls during regeneration also has a significant impact on backpressure increase.
[0023] A second method aspect of the present invention is a method for capturing volatile platinum (Pt) from an exhaust gas comprising the steps of contacting the exhaust gas with a catalytic material comprising platinum (Pt) and then contacting the exhaust gas with a solid foam layer to capture or scavenge the volatile platinum (Pt).
[0024] A second use aspect of the present invention relates to the use of a solid foam layer to capture volatile platinum (Pt) in an exhaust system for treating exhaust gases produced by an internal combustion engine. Typically the exhaust system includes a catalytic material comprising platinum (Pt), and wherein the solid foam layer is positioned to contact the exhaust gases after the exhaust gases have contacted or passed through the catalytic material comprising platinum (Pt).
[0025] When platinum (Pt)-containing catalytic materials are exposed to relatively high temperatures in exhaust gases for a sufficient period of time, low levels of platinum (Pt) can volatilize from the catalytic materials. This volatile platinum (Pt) can be transported downstream to a selective catalytic reduction (SCR) catalyst or selective catalytic reduction filter (SCRF). TM Such relatively high temperatures can occur during normal use, especially in heavy duty diesel applications, or during regeneration of particulate filters. TM Pt trapped on the catalyst can have a very detrimental effect on catalyst performance because it can oxidize ammonia (NH3). x Selective catalytic reduction of NO xThe NH3 for the purpose of reducing the conversion can be consumed and desired secondary emissions can be generated. The problem of Pt volatilization is described in WO 2013 / 088133, WO 2013 / 088132, WO 2013 / 088128 and WO 2013 / 050784.
[0026] Any reference to a "solid foam layer" in the method or use aspects of the invention above generally refers to a solid foam layer as obtained or obtainable by the method of the invention for coating a substrate with a foam.
[0027] In a second method and use embodiment of the invention, the exhaust gas may contain volatile platinum (Pt) when a catalytic material containing platinum (Pt) is exposed to a temperature of ≧700° C.
[0028] Generally, volatile platinum may be present in the exhaust gas (ie, in the exhaust system) when the temperature of the exhaust gas is ≧700°C, such as ≧800°C, preferably ≧900°C. [Brief description of the drawings]
[0029] [Figure 1a] 1 shows an image from an optical microscope of the fresh foam of Sample I of Example 2 (magnification 5x, scale bar 0.20 mm). [Figure 1b] 1 shows an image from an optical microscope of the fresh foam of Sample I of Example 2 (magnification 5x, scale bar 0.25mm). [Diagram 2] 1 shows a scanning electron microscopy (SEM) image of Example 3. [Diagram 3] 4 shows an image of a coating of the suspension in Example 4a on a segment of a substrate after cutting longitudinally. [Figure 4] 4 shows SEM images of the coated filter in Example 4a, where 4a shows the coating surface and 4b shows its cross-section. [Diagram 5] 5 shows SEM images of the coated filter in Example 4b, 5b showing the coating surface, 5a and 5c showing cross-sectional views thereof. [Figure 6] 6 shows SEM images of the coated filter in Example 4c, 6a showing the coating surface and 6b showing a cross-sectional view. [Figure 7] 1 shows an optical microscope image of the coated filter in Example 5a. [Figure 8] 4 shows an optical microscope image of the coated catalyst in Example 5b. [Figure 9] 9A and 9B show microscopic images of foam capture areas for volatile Pt dosed into the DOC formulation of Example 7 viewed perpendicular to the substrate channels, with FIG. 9a showing the foam coating and FIG. 9b showing the non-foamed conventional coating. [Figure 10] 10A-10C show SEM images of a section of the exit zone of the monolith shown in Figure 9, viewed parallel to the substrate channel. Figure 10a shows the foam coating, and Figure 10b shows the non-foamed conventional coating. [Figure 11] 1 is a chart showing the NOx conversion activity of aged SCR cores behind a DOC core with and without a volatile Pt foamed capture region when performed in an SCR SCAT test, which shows that the aged SCR core behind Example 7 (with foam coating solution) maintains higher NOx conversion activity than the aged SCR core behind Example 7 without the foam coating. [Figure 12] 1 shows an X-ray image of the coated monolith from Example 7, which includes the DOC coating of Example 6, which includes a foam capture region for volatilized Pt. In this figure, the outlet is at the top of the image, and a short (6-10 mm) foam coating is visible as a dark band directly over the outlet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The present invention provides a method of coating a substrate with a foam, the foam being a stabilized particle (herein referred to as a "particulate stabilized foam").
[0031] The method includes (a) introducing foam into a substrate (e.g., a substrate containing a plurality of channels) through the open ends of the channels at a first end of the substrate. This step is a step of applying foam to the interior of the substrate and onto the channel walls. The method for introducing liquid into a substrate described in any of WO 99 / 47260, WO 2011 / 080525, WO 2014 / 195685 and WO 2015 / 145122 (all of which are incorporated herein by reference) can be used to introduce foam into a substrate. In these methods, foam is used instead of liquid (e.g., washcoat).
[0032] (a) The step of introducing foam into the substrate through the open ends of the channels at the first end of the substrate may include the steps of: (i) placing a restraining means on top of the first end of the substrate, (ii) dispensing foam, preferably a predetermined amount of foam, into the restraining means, and (iii) [1] applying a vacuum to the open ends of the channels at the second end of the substrate (i.e., to pull the foam into the substrate through the open ends of the channels at the first end) and / or [2] applying pressure to the open ends of the channels at the first end of the substrate (i.e., to push or blow the foam into the substrate through the open ends of the channels at the first end). The first end of the substrate is the top end of the substrate and the second end of the substrate is the bottom end of the substrate. When step (a) includes administering foam to the restraining means on top of the first end of the substrate, the method may or may not include, and preferably does not include, the additional step of (b) applying (i) a vacuum to the open ends of the channels at the second end of the substrate, and / or (ii) pressure to the open ends of the channels at the first end of the substrate.
[0033] Alternatively, (a) introducing foam into the substrate through an open end of a channel at a first end of the substrate may comprise (i) holding the substrate substantially vertically and (ii) forcing or injecting foam, preferably a predetermined amount of foam, into the substrate (e.g., through the open end of the channel at the first end). Typically, the first end of the substrate is the bottom end of the substrate (and the second end of the substrate is the top end of the substrate).
[0034] Generally, it is preferred that the foam be introduced into the substrate against gravity through the open ends of the channels at the lower end (i.e., first end) of the substrate, such as by forcing or injecting the foam into the substrate.
[0035] The foam may be introduced to the substrate in a stepwise or continuous manner (e.g., without a break). Typically, it is preferred that the foam is introduced to the substrate continuously until the substrate is coated with a dose (i.e., a single dose) of foam.
[0036] Generally, step (a) involves introducing a foam in a predetermined amount.
[0037] The term "predetermined amount" as used herein refers to a total amount of foam to be introduced to a substrate sufficient to obtain a particular product characteristic, e.g., a desired coating specification. The amount is "predetermined" in the sense that it is determined offline in routine experiments to find the total amount of foam required to achieve the desired product characteristics. Such a predetermined amount is easily determinable and can be found using other methods or devices in the art for coating substrates (see, e.g., WO 99 / 47260, WO 2011 / 080525, WO 2014 / 19568, and WO 2011 / 145122).
[0038] The predetermined amount may range from 1 to 300 grams.
[0039] The predetermined amount can be a predetermined volume and / or a predetermined mass of foam. Preferably, the predetermined amount is a predetermined volume. The predetermined volume can be achieved by using a predetermined mass of known density. Typically, the predetermined volume is based on the volume of the substrate to be coated.
[0040] The predetermined volume can be 500 mL. The predetermined volume can be 150 mL or less, 100 mL or less, 75 mL or less, or 50 mL or less.
[0041] The predetermined volume may be 1 to 200% of the volume of the channel to be coated, for example 1 to 150%, preferably 1 to 100% (eg 1 to 80%) of the volume of the channel to be coated.
[0042] Typically, the predetermined amount is a single dose of foam.
[0043] As used herein, the term "single dose" refers to the amount of foam to coat a single substrate, typically to meet a desired product specification.
[0044] When step (a) includes (ii) forcing or injecting foam into the substrate, this may be (ii) using a piston to force or inject the foam, preferably a predetermined amount of foam. The piston may be located within a housing. Preferably, the piston is a reciprocating piston within the housing. Preferably, the housing has a delivery chamber.
[0045] It can be difficult to control the coating of the washcoat to a short coating depth on the substrate because at some point during the process, a pre-measured dose of the washcoat must spread to cover the facial area of the substrate. This spreading may be on the surface of the substrate or on another surface. Thus, the smaller the dose, the more difficult it is to achieve that spreading.
[0046] More specifically, it can be difficult with current methods of coating substrates with washcoats to precisely deliver a relatively small amount of washcoat to a particular coat depth, especially with any degree of accuracy. This is especially true when the washcoat is applied partially as a top layer over a bottom layer, with the top layer designed to cover only a small portion of the bottom layer. This is especially true when the top layer is designed to be a relatively thinner coating than the bottom layer. When the top layer is placed over the bottom layer, the thickness of the top layer is important, and even important in obtaining the desired conversion in the system when the diffusion of exhaust gas through the top layer is important. For example, in an ammonia slip catalyst, a layer containing an ammonia oxidation catalyst can be placed above or below a layer containing an SCR catalyst. The coating depth of the ammonia oxidation layer can be more precisely controlled using the foam coating described herein.
[0047] The emission control devices and methods for their manufacture of the present invention allow for improved sequential passage of gas into and through various zones of the emission control device containing different catalytic materials or different amounts of catalytic materials when the catalyst or catalytic material is present in a continuous or zoned structure.
[0048] The foam is introduced and coated onto the channel walls to provide a solid foam layer of a predetermined length. The predetermined length may be 0.1-100% of the length of the channel, such as 0.2-100% (e.g. 1-100%). The predetermined length is preferably 1-60% (e.g. 0.1-50%) of the length of the channel, such as 1-20% of the length of the channel, particularly preferably 0.5 to 15% of the length of the channel, more preferably 1 to 10% of the length of the channel. For the avoidance of doubt, the predetermined length refers to the length of the solid foam layer after drying and / or baking. The length of the particulate stabilized foam initially coated on the substrate may be longer, shorter or the same as the predetermined length of the solid foam layer.
[0049] The predetermined length is 100 mm or less. The predetermined length is preferably 80 mm or less, 70 mm or less, 50 mm or less (e.g., 30 mm or less), 25 mm or less, 20 mm or less, 15 mm or less (e.g., 12 mm or less), 10 mm or less (e.g., 8 mm or less), or 5 mm or less. The predetermined length depends on the length of the substrate and may be limited by that length.
[0050] Typically, the foam can be coated onto the channel walls to provide a uniform, predetermined length. The expression "uniform, predetermined length" refers to a difference between each solid foam layer on the wall of the channel of 20 mm or less, typically 5 mm or less (e.g. 2 mm or less), preferably 1.5 mm or less, more preferably 1 mm or less, especially 0.8 mm or less.
[0051] In the method of the present invention, the substrate is a coated substrate (e.g., prior to step (a) of introducing the foam to the substrate) or an uncoated substrate. When the substrate is a coated substrate, the foam can be introduced into the coated substrate and onto the coating of the substrate. In general, it is preferred that the substrate is an uncoated substrate (i.e., prior to the introduction of the foam).
[0052] The method of the invention may include step (b) applying (i) a vacuum to the open ends of the channels at the second end of the substrate, and / or (ii) pressure to the open ends of the channels at the first end of the substrate.
[0053] In a first embodiment, step (b) may comprise applying a vacuum to the open ends of the channels at the second end of the substrate during or after step (a). Preferably, the substrate is not inverted prior to application of the vacuum (i.e. during or after step (a)).
[0054] In a second embodiment, step (b) may include (i) sealingly retaining the foam within the substrate; (ii) inverting the substrate containing the retained foam; and (iii) applying a vacuum to the open ends of the channels at the second end of the substrate. In a second embodiment, step (b) is performed after step (a). Typically, the first end of the substrate is the bottom end of the substrate, and the second end of the substrate is the top end of the substrate. After inversion, the second end of the substrate is lower than the first end of the substrate.
[0055] Typically, the method of the present invention further comprises a step (c) of drying and / or calcining the substrate containing the particulate stabilized foam (i.e., to obtain a solid foam layer disposed or supported on the substrate), which step (c) is carried out after step (a) or after steps (a) and (b).
[0056] The substrate may be dried at 75 to 150° C., such as 80 to 150° C., preferably 85 to 125° C. (e.g. for 5 to 60 minutes, especially 10 to 30 minutes). The drying step may be carried out to fix the foam onto the substrate.
[0057] The substrate may be fired at a temperature up to 750°C, such as from 150 to 750°C (eg, greater than 150°C and up to 750°C), for example from 300 to 600°C, more preferably from 400 to 550°C.
[0058] The method of the present invention includes a step (d) of repeating (a) or (c), or repeating (a), (b) and (c), with a second particulate stabilized foam comprising a second particulate material. The second particulate stabilized foam may be the same or different from the first particulate stabilized foam. The difference may be based on the foam composition, the foam dosage, the foam solids content and / or the foam viscosity. The coating may be performed at different locations, using different amounts and / or different coating lengths. For example, the first foam coating or any subsequent additional coatings may start from the same or other open end of the channel as the previous foam coating.
[0059] The method of the present invention includes the step of introducing a particulate stabilized foam into a substrate. References to "particulate stabilized foam" as used herein generally refer to wet particulate stabilized foam unless otherwise indicated. The term "particulate stabilized foam" is well known in the art and refers to Pickering foam. Particulate stabilized foam is fundamentally different from interfacially stabilized foam.
[0060] Particulate stabilized foams may be obtained from a direct foaming process, which involves the steps (i) of preparing a suspension of particulate material in an aqueous medium (e.g., a liquid such as water); and (ii) of foaming the suspension, e.g., by introducing a gas into the suspension, to produce a particulate stabilized foam. By removing the liquid by heating, a solid foam material may be produced.
[0061] When the particulate material comprises or consists of a ceramic material (defined below), the method of the invention further comprises the step of impregnating the solid foam layer with a solution, preferably an aqueous solution, comprising or consisting essentially of a catalytically active metal, a sorbent or a precursor thereof. This step is preferably carried out after (c) drying and / or calcining the substrate containing the particulate stabilized foam. The solution typically does not comprise a ceramic material, as described below.
[0062] The method may include the further step of drying and / or calcining the substrate after the step of impregnating the solid foam layer with the solution. Precursors of catalytically active metals (e.g., Pt, Pd, Cu, or Fe) or sorbents (e.g., alkaline earth metals, e.g., Mg, Ba, or Sr) typically form catalytically active metals or sorbents after calcination.
[0063] Typically, the particulate material has a median particle size (e.g. d ) of 1 nm to 50 μm (e.g. 20 nm to 50 μm), preferably 2 nm to 20 μm (e.g. 20 nm to 20 μm), for example 2 nm to 10 μm (e.g. 20 nm to 10 μm), more preferably 2 nm to 7 μm (e.g. 20 nm to 7 μm). 50 ) d50 can be measured by Malvern Mastersizer 2000 light scattering method.
[0064] The particulate material may preferably have a median particle size of from 1 μm to 10 μm, preferably from 2 μm to 7 μm.
[0065] Generally, the particulate material has a diameter of 1 nm to 50 μm (e.g., 20 nm to 50 μm, preferably 10 μm to 20 μm), preferably 2 nm to 18 μm (e.g., 20 nm to 18 μm, preferably 15 μm to 18 μm). 90 The particle size is d 90 The particle size is d 50 Larger than particle size. d 90 can be measured by Malvern Mastersizer 2000 light scattering method.
[0066] When the emission control device includes a solid foam layer for capturing volatile platinum (Pt), the particulate material has a diameter of 10 μm to 20 μm, preferably 15 μm to 18 μm. 90 It is preferred that the particle size is 0.1 to 1.0 mm.
[0067] When the particulate material has a larger median particle size, it can be milled to obtain the desired median particle size. Good foams can be obtained with narrow or broad particle size distributions.
[0068] Particulate materials that have been pretreated with surface modifiers (including particulate materials that have been pretreated with amphiphiles) may be used.
[0069] In the direct foaming process described above, step (i) may involve preparing a suspension of particulate material in an aqueous medium (eg liquid) containing the amphiphilic substance.
[0070] Amphiphiles are compounds that contain a tail linked to a head group. The tail is generally described as non-polar and may be aliphatic (straight chain alkyl or cycloalkyl) or aromatic (phenyl or naphthyl) and may bear one or more substituents. Such substituents include alkyl groups, e.g., -C, where n<8. n H 2n+1 , an aryl group (such as phenyl or substituted phenyl), -OH or -NH2. A preferred tail is an optionally substituted linear carbon chain containing from 2 to 8 carbon atoms. The head group attached to the tail is preferably an ionic or polar group and may be selected from phosphate, phosphonate, phosphinate, sulfate, sulfonate, carboxylate (i.e. COOH), carboxylate ester, gallate ester, amide, amine including cyclic amine and -OH.
[0071] Suitable amphiphiles include, but are not limited to, carboxylic acids, phenolic derivatives such as alkyl-substituted phenols, ester derivatives of gallic acid (3,4,5-trihydroxybenzoate), catechol derivatives (e.g., alkyl-catechols), amines (e.g., alkyl-substituted amines and catecholamines), and amino acids.
[0072] Particularly preferred amphiphiles are C2-C6 carboxylic acids and their esters, such as valeric acid, butyric acid and propionic acid, and C2-C6 gallate esters, such as propyl gallate. Furthermore, applicants have found that particularly stable foams can be prepared using amino acids, particularly alpha-amino acids, where the amino group is attached to the carbon atom adjacent to the carboxylate head group. Preferred alpha-amino acids include one or more of valine, isoleucine, leucine, phenylalanine and tryptophan. Methionine can be used if the sulfur content of the resulting foam allows. Less preferred alpha-amino acids include alanine and tyrosine. Particularly preferred alpha-amino acid amphiphiles include one or more of leucine, isoleucine and phenylalanine. The D, L or DL forms of each can be used. A particularly suitable amino acid is phenylalanine. DL-phenylalanine can be used.
[0073] The pH of the suspension may be adjusted before the amphiphile is included, but may not need to be adjusted, for example, the pH may be adjusted to a pH at which the surface charge of the particulate material is sufficiently high for electrostatic stabilization, or to a pH at which the solubility of the amphiphile is increased.
[0074] Depending on the charge of the surface to be coated, negatively or positively charged head groups can be selected. For Al2O3, negatively charged head groups are suitable at low pH conditions, i.e., below the isoelectric point, here pH<9, especially pH 4-5. The above head groups and further similar groups can be used to modify a wide range of ceramic particles, especially metal oxides.
[0075] Surface modification can be achieved through physical or chemical adsorption of negatively or positively charged amphiphilic molecules to a suitable, preferably oppositely charged, surface that leaves the hydrophobic tail in contact with the aqueous phase. For positively charged alumina particles, adsorption can be performed with carboxylic acids in water at pH 4.75. By varying the anchoring polar head group of the amphiphile, the alumina surface can also be modified under neutral pH conditions, for example using alkyl gallates as adsorbed molecules. This amphiphile can also be used to lyophobize the surfaces of various other amphoteric and basic oxides. Alternatively, the surfaces of acidic oxides such as silica, silicon carbide and silicon nitride can be lyophobized using amphiphiles with amine-containing head groups.
[0076] For in-situ lyophobization of particles, the amphiphile may be applied in an amount of less than 15% by weight of the particle, preferably <5% by weight. The minimum amount of amphiphile to be present is about 0.1% by weight, preferably about 1% by weight. Amounts ranging from 0.02 to 2 mmol per gram of solids of amphiphile may be used. The actual amount of modifier used is selected depending on the desired final viscosity, since the amphiphile, in addition to the other components of the suspension, also affects the viscosity of the foam.
[0077] The particulate material typically acts as a foam stabilizer.
[0078] Particulate materials of different shapes can be used as foam stabilizers, provided the particle size is within the appropriate dimensions, i.e., ceramic particles have been found to be spherical, polygonal platelet, needle-like, fibrous, rod-like, single crystal, etc. The particles themselves can be dense, i.e. non-porous, or porous, or a mixture of dense and porous particles can be used.
[0079] Typically, the particulate stabilized foam contains cells having a diameter, preferably an average diameter, of 1 μm to 1 mm, preferably 10 μm to 300 μm. The cell diameter and average diameter can be determined by optical microscopy.
[0080] After step (c) of the process, some of the cells in the particulate stabilised foam may collapse or partially collapse.
[0081] Typically, after step (c), at least 5%, 10%, 20%, 30%, 40% or 50% of the cells of the particulate stabilized foam have collapsed. Additionally or alternatively, after step (c), at least 60%, 70%, 80%, 90% or 95% of the cells of the particulate stabilized foam have collapsed.
[0082] The density of the foam is typically from 0.1 to 1.2 g / ml.
[0083] The foam comprises a particulate material. The particulate material may be a ceramic material, a catalytic material, or a sorbent material. The term "sorbent" in this context refers to a material that is a sorbent (e.g., NO x or for hydrocarbons). The sorbent can be, for example, (i) an alkaline earth metal (e.g., Ca, Mg, Ba, Sr) or their oxides, hydroxides, or carbonates, or (ii) a hydrocarbon absorbent, such as a zeolite, preferably a non-transition metal exchanged zeolite.
[0084] Particle-stabilized foams can be prepared using suspensions of powders that include or consist essentially of ceramic materials, catalytic materials, sorbent materials, or precursors thereof. Foams can also be prepared using metal powders.
[0085] The particulate material may be a ceramic material and / or a catalytic material, preferably a catalytic material.
[0086] The ceramic material may comprise or consist essentially of a refractory oxide, a ceramic compound (e.g., SiC), a metal aluminate, a molecular sieve (e.g., a zeolite), or a mixture of two or more thereof. Ceramic materials are typically suitable for use as support materials such as catalytically active metals or sorbents. A solid foam layer comprising a ceramic material may be treated with a catalytically active metal or sorbent in a subsequent process step (e.g., by an impregnation step).
[0087] The refractory oxide may be selected from the group consisting of alumina, silica, titania, magnesia, zirconia, ceria, lanthana, and mixed or composite oxides of two or more thereof. For example, the refractory oxide may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, silica-alumina, titania-alumina, zirconia-alumina, ceria-alumina, titania-silica, zirconia-silica, zirconia-titania, ceria-zirconia, ceria-zirconia-alumina, and alumina-magnesium oxide.
[0088] The catalytic material typically comprises a catalytically active metal supported on a support material. When the support material comprises a molecular sieve, such as a zeolite, the catalytically active metal may be supported on the molecular sieve or zeolite, such as a metal-exchanged molecular sieve or zeolite.
[0089] Typically, the catalytically active metal is at least one transition metal selected from iron, copper, nickel, gold, platinum, palladium, rhodium and ruthenium.
[0090] Typically the support material is a refractory oxide, a metal aluminate or a molecular sieve (e.g. a zeolite) as defined above. The transition metal and precious metal content in such catalysts can be up to 85% by weight, but is preferably in the range of 0.1-35% by weight.
[0091] When the particulate material comprises a catalytic material, the loading of catalytically active metal, preferably a transition metal, is preferably between 0.1 and 300 g.ft -3 , preferably 0.5 to 300 g.ft -3 It is.
[0092] Typically, the sorbent material is x The storage material or hydrocarbon absorbent is typically a zeolite, preferably a non-transition metal exchanged zeolite.
[0093] In general, NO x The storage material is a NOx storage material supported on a support material. x It contains or consists essentially of a storage component. Typically, NO x The storage component is an alkali metal (e.g. potassium (K), sodium (Na) or lithium (Li), preferably potassium (K)), an alkaline earth metal (e.g. magnesium (Mg), calcium (Ca), strontium (Sr) or barium (Ba), preferably barium (Ba)), a rare earth metal (e.g. cerium (Ce), lanthanum (La) or yttrium (Y), preferably cerium (Ce)), or an oxide, carbonate or hydroxide thereof. The support material may be a refractory oxide or a metal aluminate as defined above.
[0094] The ceramic and / or catalytic materials are used in three-way catalysts (TWC), diesel oxidation catalysts (DOC), NO x Absorber catalyst (NAC), Ammonia Slip Catalyst (ASC), Selective Catalytic Reduction (SCR) catalyst, Catalyzed Particulate Filter (Gasoline and Diesel) or SCR Catalyst on Filter (SCRF) TM ) may be suitable for use in emission control devices.
[0095] The particulate stabilized foams may have a solids content of 1-50%, 2-45%, 3-45%, 3-35% or 5-30% by weight, more preferably 10-25% by weight. The solids content of the foam is defined as the weight ratio between the particulate material suspended in the liquid and the total weight of the suspension (liquid + solids) before the foaming process.
[0096] After performing step (c) of the method of the invention, a solid foam layer is obtained that is disposed or supported on a substrate. The invention also relates to an emission control device that includes a solid foam layer that is disposed or supported on a substrate. Typically, the solid foam layer includes a particulate material. The particulate material may include a catalytic material. The solid foam layer is further described below.
[0097] The solid foam layer may be disposed or supported directly on the substrate (i.e., the solid foam layer is in direct contact with the surface of the substrate) and / or the solid foam layer may be disposed over a layer, such as a layer derived from a washcoat.
[0098] When the solid foam layer is disposed or supported directly on the substrate, the solid foam layer is substantially localized on the channel walls. By "substantially localized on the channel walls" is meant that <50%, preferably <75% (e.g. <90%) of the solid foam layer is localized on the channel walls rather than in (i.e. within) the pores of the channel walls. However, it is recognized that trace amounts of foam may migrate or diffuse into the walls.
[0099] Generally, the solid foam layer comprises an open cell structure. The term "open cell structure" as used herein means that a portion of the cell volume is interconnected. Typically, more than 20% of the cell volume, preferably more than 30%, 40% or 50% of the cell volume are interconnected. There may be open flow paths through the open cell structure of the solid foam layer. In an open cell structure, the pores are interconnected with each other.
[0100] The solid foam layer may have a median pore diameter of from 1 to 100 μm, preferably from 5 to 80 μm.
[0101] The solid foam layer generally comprises cells or cell-like structures having a size distribution in the range of 5 μm to 500 μm, 50 μm to 250 μm, 50 μm to 200 μm, or 5 μm to 140 μm. The size distribution can be measured using SEM.
[0102] The solid foam layer may comprise a partially collapsed structure. At least 5%, 10%, 20%, 30%, 40% or 50% of the solid foam layer may have a collapsed structure. The solid foam layer may have a substantially collapsed structure. Thus, at least 60%, 70%, 80%, 90% or 95% of the solid foam layer has a collapsed structure.
[0103] Typically, the thickness of the solid foam layer is 500 μm or less, 400 μm or less, 350 μm or less, 300 μm or less, 200 μm or less, 160 μm or less, or 150 μm or less.
[0104] When the solid foam layer includes a partially collapsed structure, the thickness of the dense layer (eg, the collapsed portion of the solid foam layer) is between 2 μm and 400 μm, 5 μm and 300 μm, 10 μm and 200 μm, or 20 μm and 150 μm.
[0105] The emission control device may have a washcoat loading or impregnation loading (e.g., of catalytically active material or sorbent) on and / or within the substrate for each layer or combination of two or more layers, which may be greater than or equal to about 0.1 g / in 3 Approximately 8g / in 3 , more preferably about 0.5 g / in 3 Approximately 6g / in 3 , and even more preferably about 1 g / in 3 Approximately 4g / in 3 It is.
[0106] The washcoat loading or impregnation loading on and / or within the substrate for each layer or combination of two or more layers is ≥ 1.00 g / in 3 , e.g. ≧1.2g / in 3 , ≥ 1.5g / in 3 , ≥ 1.7g / in 3 or ≧2.00g / in 3 (For example, about 1.5 g / in 3 from about 2.5g / in 3 ) is preferred.
[0107] The term "washcoat" is a term widely recognized in the art and refers to a mixture of ceramic, catalytic or sorbent materials, and optionally one or more other materials, such as binders, promoters or stabilizers.
[0108] Generally, washcoat loadings range from about 0.1 to about 5.0 g.in. -3 (For example, 0.6 to 2.5 g.in-3 or 0.1 to about 1.0 g.in -3 , preferably 0.1 to 0.6 g.in -3 ).
[0109] Typically, the washcoat is between 0.1 and 300 g.ft -3 Catalytically active metals or NO x In another further embodiment, the loading of a catalytically active metal or NO x The storage component is 0.5 to 300 g.ft -3 The catalytically active metal is typically a platinum group metal (PGM), such as platinum, palladium and / or rhodium.
[0110] Substrates for use in the methods of the present invention and for emission control devices are well known in the art.
[0111] Generally, it is preferred that the substrate is a honeycomb monolith substrate. As used herein, the term "honeycomb monolith substrate" refers to a substrate having a plurality of channels extending longitudinally along the length of the substrate, each channel having at least one open end (i.e., for exhaust gas flow). Typically, the channels are formed between a plurality of walls. The channels may have an irregular cross section and / or a regular cross section. When the channels have a regular cross section, the cross section is not limited to a hexagonal cross section, but may be, for example, rectangular or square.
[0112] The honeycomb monolith substrate may be a flow-through honeycomb monolith substrate. Thus, the honeycomb monolith substrate typically includes a plurality of channels extending therethrough, each of which is open at both ends (i.e., an inlet open end and an outlet open end). In general, a flow-through honeycomb monolith substrate is different from a partial filter honeycomb monolith substrate. Typically, a flow-through honeycomb monolith substrate does not include collection elements such as a plurality of deflectors in the walls.
[0113] The honeycomb monolith substrate can be a honeycomb monolith filter substrate, such as a wall-flow honeycomb monolith substrate, that is capable of capturing or removing particulate matter (PM), such as soot particles, in exhaust gases produced by internal combustion engines, particularly compression ignition engines (e.g., diesel engines).
[0114] In a wall-flow honeycomb monolith substrate, the honeycomb monolith substrate comprises a plurality of channels, each of which has an open end and a closed end (e.g., plugged end). Typically, each channel is separated from an adjacent channel by a porous structure (e.g., a porous wall). In general, each channel having an open end at a first end of the substrate and a closed (e.g., plugged) end at a second (i.e., opposite) end of the substrate is typically adjacent to a channel having a closed (e.g., plugged) end at the first end of the substrate and an open end at the second (i.e., opposite) end of the substrate. When the first end of the substrate is disposed at the upstream end, (i) each channel having an open end at the first end of the substrate and a closed end at the second end of the substrate is an inlet channel, and (ii) each channel having a plugged end at the first end of the substrate and an open end at the second end of the substrate is an outlet channel. Preferably, each inlet channel is alternately separated from an outlet channel by a porous structure (e.g., a porous wall), and vice versa. Thus, the outlet channels are vertically and laterally adjacent to the inlet channels and vice versa. Fluid communication between the inlet and outlet channels is through the porous structure (e.g., porous walls) of the substrate. When viewed from either end, the alternating blocked (e.g., closed) and open ends of the channels give the appearance of a chessboard.
[0115] The substrate can be a partial filter substrate (see, for example, the partial filter substrates disclosed in WO 01 / 80978 or EP 1057519). Typically, a partial filter substrate has a collection element (e.g., for particulate matter such as soot particles) and a number of channels (i.e., for the exhaust gas flowing therethrough), each channel having at least one open end (preferably, each channel has two open ends (i.e., both ends of each channel are open)). In general, a partial filter substrate has a number of walls that define the boundaries of the channels. Typically, the collection element is a number of deflections in the walls. Each wall may have no deflections or one or more deflections. Each deflection acts as an obstacle for any particulate matter in the exhaust gas flowing through the substrate. Each deflector may have a flap or wing-like shape, and typically each deflector projects outward (e.g., at an angle) from the plane of the wall. Preferably, each deflector is combined with an opening in the wall of the substrate. Each opening in the wall allows exhaust gas to flow from one channel to an adjacent channel.
[0116] Generally, the substrate is a ceramic material or a metal material. When the substrate is a ceramic material, typically the ceramic material can be selected from the group consisting of silicon carbide (SiC), aluminum nitride, silicon nitride, aluminum titanate, alumina, cordierite (SiO2-Al2O3-MgO), mullite, pollucite and thermet (e.g., Al2O3 / Fe, Al2O3 / Ni or B4C / Fe, or a composite containing two or more segments thereof). When the substrate is a metal material, typically the metal material is selected from the group consisting of Fe-Cr-Al alloy, Ni-Cr-Al alloy and stainless steel alloy.
[0117] The inventors have developed two advantageous embodiments of the emission control device of the present invention which include a solid foam layer.
[0118] In a first emission control device embodiment, the emission control device is an SCR catalyst. The solid foam layer includes a particulate material that is a metal oxide-based SCR catalyst formulation, a molecular sieve-based SCR catalyst formulation, or a mixture thereof. Such SCR catalyst formulations are known in the art.
[0119] Metal oxide-based SCR catalyst formulations typically contain vanadium or tungsten, or mixtures thereof, supported on a refractory oxide, which may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, and combinations thereof.
[0120] Metal oxide-based SCR catalyst formulations include titania (e.g., TiO2), ceria (e.g., CeO2), and mixed or composite oxides of cerium and zirconium (e.g., CeO2). x Zr (1-x) Preferably, the catalyst comprises or consists essentially of an oxide of vanadium (e.g., V2O5) and / or an oxide of tungsten (e.g., WO3) supported on a refractory oxide selected from the group consisting of: 02, 02, where x=0.1 to 0.9, preferably x=0.2 to 0.5).
[0121] When the refractory oxide is titania (e.g., TiO2), preferably the vanadium oxide concentration is 0.5 to 6 wt. % and / or the tungsten oxide (e.g., WO3) concentration is 5 to 20 wt. % (e.g., of the metal oxide-based SCR formulation). More preferably, the vanadium oxide (e.g., V2O5) and tungsten oxide (e.g., WO3) are supported on titania (e.g., TiO2).
[0122] When the refractory oxide is titania (e.g., CeO2), preferably the concentration of vanadium oxide is 0.1 to 9 wt. % (e.g., of a metal oxide-based SCR formulation) and / or the concentration of tungsten oxide (e.g., WO3) is 0.1 to 9 wt. %.
[0123] In general, it is preferred that the metal oxide-based SCR catalyst formulation comprises or consists essentially of an oxide of vanadium (e.g., V2O5) and optionally an oxide of tungsten (e.g., WO3) supported on titania (e.g., TiO2).
[0124] The first selective catalytic reduction composition may comprise or consist essentially of a molecular sieve-based SCR catalyst formulation. The molecular sieve-based SCR catalyst formulation comprises a molecular sieve that is optionally a transition metal-exchanged molecular sieve. The SCR catalyst formulation preferably comprises a transition metal-exchanged molecular sieve.
[0125] In general, the molecular sieve-based SCR catalyst formulation may include a molecular sieve having an aluminosilicate framework (e.g., zeolite), an aluminophosphate framework (e.g., AlPO), a silicoaluminophosphate framework (e.g., SAPO), a heteroatom-containing aluminosilicate framework, a heteroatom-containing aluminophosphate framework (e.g., MeAlPO, where Me is a metal), or a heteroatom-containing silicoaluminophosphate framework (e.g., MeAPSO, where Me is a metal). The heteroatoms (i.e., in the heteroatom-containing framework) may be selected from the group consisting of boron (B), gallium (Ga), titanium (Ti), zirconium (Zr), zinc (Zn), iron (Fe), vanadium (V), and combinations of two or more thereof. The heteroatoms are preferably metals (e.g., each of the heteroatom-containing frameworks above may be a metal-containing framework).
[0126] The molecular sieve-based SCR catalyst formulation preferably comprises or consists essentially of a molecular sieve having an aluminosilicate framework (e.g., zeolite) or a silicoaluminophosphate framework (e.g., SAPO). More preferably, the molecular sieve has an aluminosilicate framework (e.g., zeolite).
[0127] When the molecular sieve has an aluminosilicate framework (e.g. the molecular sieve is a zeolite), the molecular sieve typically has a silica to alumina molar ratio (SAR) of from 5 to 200 (e.g. from 10 to 200), preferably from 10 to 100 (e.g. from 10 to 30 or from 20 to 80), for example from 12 to 40, more preferably from 15 to 30.
[0128] Typically, the molecular sieve is microporous. Microporous molecular sieves have pores with diameters of 2 nm or less (e.g., according to the IUPAC definition of "microporous" [see Pure & Appl. Chem., 66(8),(1994), 1739-1758]).
[0129] The molecular sieve-based SCR catalyst formulation may include a small pore molecular sieve (e.g., a molecular sieve having a maximum ring size of 8 tetrahedral atoms), a medium pore molecular sieve (e.g., a molecular sieve having a maximum ring size of 10 tetrahedral atoms), or a large pore molecular sieve (e.g., a molecular sieve having a maximum ring size of 12 tetrahedral atoms), or a combination of two or more thereof.
[0130] When the molecular sieve is a small pore molecular sieve, the small pore molecular sieve may have a framework structure represented by a framework type code (FTC) selected from the group consisting of ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, GIS, GOO, IHW, ITE, ITW, LEV, KFI, MER, MON, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SIV, THO, TSC, UEI, UFI, VNI, YUG, and ZON, or mixtures and / or intergrowths of two or more thereof. Preferably, the small pore molecular sieve has a framework structure represented by an FTC selected from the group consisting of CHA, LEV, AEI, AFX, ERI, SFW, KFI, DDR, and ITE. More preferably, the small pore molecular sieve has a framework structure represented by an FTC selected from the group consisting of CHA and AEI. The small pore molecular sieve may have a framework structure represented by FTC CHA. The small pore molecular sieve may have a framework structure represented by FTC AEI. When the small pore molecular sieve is a zeolite and has a framework represented by FTC CHA, the zeolite may be chabazite.
[0131] When the molecular sieve is a medium pore molecular sieve, the medium pore molecular sieve may have a framework structure represented by a Framework Type Code (FTC) selected from the group consisting of AEL, AFO, AHT, BOF, BOZ, CGF, CGS, CHI, DAC, EUO, FER, HEU, IMF, ITH, ITR, JRY, JSR, JST, LAU, LOV, MEL, MFI, MFS, MRE, MTT, MVY, MWW, NAB, NAT, NES, OBW, -PAR, PCR, PON, PUN, RRO, RSN, SFF, SFG, STF, STI, STT, STW, -SVR, SZR, TER, TON, TUN, UOS, VSV, WEI and WEN, or mixtures and / or intergrowths of two or more thereof. Preferably, the medium pore molecular sieve has a framework structure represented by an FTC selected from the group consisting of FER, MEL, MFI and STT. More preferably, the medium pore molecular sieve has a framework structure represented by an FTC selected from the group consisting of FER and MFI. When the medium pore molecular sieve is a zeolite and has a framework represented by the FTC FER or MFI, the zeolite can be ferrierite, silicalite or ZSM-5.
[0132] When the molecular sieve is a large pore molecular sieve, the large pore molecular sieve is AFI, AFR, AFS, AFY, ASV, ATO, ATS, BEA, BEC, BOG, BPH, BSV, CAN, CON, CZP, DFO, EMT, EON, EZT, FAU, GME, GON, IFR, ISV, ITG, IWR, IWS, IWV, IWW, JSR, LTF, LTL, MAZ, ME The large pore molecular sieve may have a framework structure represented by a framework type code (FTC) selected from the group consisting of I, MOR, MOZ, MSE, MTW, NPO, OFF, OKO, OSI, -RON, RWY, SAF, SAO, SBE, SBS, SBT, SEW, SFE, SFO, SFS, SFV, SOF, SOS, STO, SSF, SSY, USI, UWY and VET, or mixtures and / or intergrowths of two or more thereof. Preferably, the large pore molecular sieve has a framework structure represented by an FTC selected from the group consisting of AFI, BEA, MAZ, MOR and OFF. More preferably, the large pore molecular sieve has a framework structure represented by an FTC selected from the group consisting of BEA, MOR and MFI. When the large pore molecular sieve is a zeolite and has a framework represented by FTC BEA, FAU or MOR, the zeolite can be beta zeolite, faujasite, zeolite Y, zeolite X or nordenite.
[0133] Generally, it is preferred that the molecular sieve is a small pore molecular sieve.
[0134] The molecular sieve-based SCR catalyst formulation preferably comprises a transition metal exchanged molecular sieve. The transition metal may be selected from the group consisting of cobalt, copper, iron, manganese, nickel, palladium, platinum, ruthenium and rhenium. Preferably, the transition metal is selected from the group consisting of copper and iron.
[0135] The transition metal may be iron. An advantage of SCR catalyst formulations containing iron-exchanged molecular sieves is that such formulations provide better NO 2 production at higher temperatures than, for example, copper-exchanged molecular sieves. xThe iron-exchanged molecular sieves also produce minimal amounts of N2O (compared to other types of SCR catalyst formulations).
[0136] The transition metal may be copper. An advantage of SCR catalyst formulations containing copper-exchanged molecular sieves is that such formulations provide excellent low temperature NO x Reductively active (e.g., low-temperature NO on iron-exchanged molecular sieves) x (which may be superior to reducing activity).
[0137] The transition metal may be present within the channels, cavities or cages of the molecular sieve or at extraframework sites on the exterior surface of the molecular sieve.
[0138] As noted above, increasing the loading of catalytic material can result in an undesirable increase in filter backpressure. For example, a selective catalytic reduction (SCR) catalyst may include V2O5 / WO3 / TiO2 and a transition metal exchanged zeolite, such as Fe / Beta zeolite or Cu / CHA. The difficulty with making such products is balancing the competing requirements of retaining catalytic activity at acceptable backpressure. It is possible to counter some of the attendant difficulties with using higher porosity filter substrates, but such substrates are more fragile and more difficult to handle. Another means of avoiding unacceptable backpressure is to limit the amount of catalytic material. However, reducing the amount of SCR catalyst can result in lower NO2. x conversion and NH3 storage capacity, which is x It is important for conversion.
[0139] Furthermore, highly complex multi-layer catalyst configurations such as DOC and NAC can be coated onto the flow-through substrate monolith. Although it is possible to coat the surface of a filter monolith, such as the inlet channel surface of a wall-flow filter, with one or more layers of a catalyst composition, a problem with coating a filtering monolith is to avoid an unnecessary increase in back pressure during use by overloading the filter monolith with a catalyst washcoat, thereby restricting gas passage therethrough. Thus, although it is not impossible to sequentially coat the surface of a filter substrate monolith with one or more different catalyst layers, it is more common to separate the different catalyst compositions in zones, for example by axially separating a front half zone and a rear half zone of the filter monolith, or by coating the inlet channel of the wall-flow filter substrate monolith with a first catalyst composition and the outlet channel of the wall-flow filter substrate monolith with a second catalyst composition.
[0140] It has been found that coating a substrate with a particulate stabilized foam can reduce the backpressure normally associated with the same substrate coated with a washcoat having a similar composition. The foam coating described herein allows for the formation of a penetrating washcoat layer, minimizing the effects of backpressure by increasing washcoat loading, thereby allowing for more catalyst coating at acceptable backpressure. The foam layer also prevents soot from entering the walls of the filter or other substrate, minimizing the effect of soot on backpressure.
[0141] When the emission control device is an SCR catalyst, the substrate is typically a honeycomb monolith substrate, preferably a flow-through honeycomb monolith substrate or a wall-flow honeycomb monolith substrate, more preferably a wall-flow honeycomb monolith substrate.
[0142] The substrate can be a cordierite flow-through monolith, a metal flow-through monolith, a cordierite particulate filter, a silicon carbide particulate filter or an aluminum titanate particulate filter.
[0143] When the substrate is a wall-flow honeycomb monolith substrate, such as a particulate filter, typically the substrate has a porosity of 40 to 70%, preferably 45 to 65%, such as 50 to 65% (e.g. 55 to 65%). Additionally or alternatively, the substrate may have an average pore size of 8 to 45 μm, preferably 10 to 30 μm (e.g. 10 to 25 μm), especially 15 to 25 μm. The average pore size may be determined by mercury porosimetry.
[0144] In a second emission control device embodiment, the emission control device includes a substrate for capturing volatile platinum (Pt) and a solid foam layer, the solid foam layer preferably having an open cell structure.
[0145] The solid foam layer for capturing volatile platinum (Pt) comprises or essentially consists of a capture material. Particulate material is typically the capture material. Suitable capture materials are described in WO 2013 / 088133, WO 2013 / 088132, WO 2013 / 088128, WO 2013 / 050784 and WO 2016 / 128720 (all of which are incorporated herein by reference).
[0146] The capture material is (a) Particles of refractory oxide, preferably ≦about 50 m 2 Particles of a refractory oxide having an average specific surface area of 1 / g, and / or (b) particles of Pt alloy metal, preferably having an average particle size of ≧about 10 nm and / or a dispersion of ≦about 10%. comprises or consists essentially of
[0147] Typically, the solid foam layer or capture material for capturing volatile platinum (Pt) is 0.1 to 3.5 g in -3 , preferably 0.2 to 2.5 g in -3 , more preferably 0.3 to 2.0 g in -3 , and even more preferably 0.5 to 1.75 g in -3 (e.g. 0.75 to 1.5 g in -3 ) refractory oxide particle loading.
[0148] The captured material is ≦50m 2 / g(<about 50m 2 / g), e.g. ≦about 40m 2 / g(<about 40m 2 / g), preferably ≦about 30m 2 / g(<about 30m 2 / g), more preferably ≦about 20m 2 / g(<about 20m 2 / g), and even more preferably ≦about 10 m 2 / g(<about 10m 2 The refractory oxide particles may comprise or consist essentially of refractory oxide particles having an average specific surface area of 1000 nm to 1000 nm / g. The average specific surface area (SSA) of the refractory oxide particles may be determined by nitrogen physisorption at -196°C using a volumetric method. The average SSA is determined using the BET adsorption isotherm.
[0149] Refractory oxide is <100 microns d 90 The refractory oxide may preferably have a d of <75 microns, such as <50 microns (e.g. <30 microns), more preferably <20 microns. 90 may have.
[0150] Typically, refractory oxides have a d of >0.1 microns. 90 The refractory oxide may have a d of >1.0 micron, e.g., >5.0 micron. 90 It is preferred that the compound has the formula:
[0151] The refractory oxide particles for use according to the second emission control device embodiment of the present invention have a relatively low average specific surface area compared to the average specific surface area of the same refractory oxide particles used as a support material (e.g., for catalytically active metals such as platinum group metals) in prior art emission control devices (e.g., DOC, CSF, or NSC). In general, small refractory oxide particles with large average specific surface area are used to maximize catalytic activity. In contrast, the refractory oxide particles for use according to the present invention are relatively large (i.e., generally much larger than when used as a support material in prior art emission control devices).
[0152] ≦About 50m 2 Refractory oxides having an average specific surface area of 1000 nm to 1000 nm are known in the art and are commercially available.
[0153] The refractory oxide may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, and mixed or composite oxides thereof, such as mixed or composite oxides of two or more thereof. For example, the refractory oxide may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, silica-alumina, titania-alumina, zirconia-alumina, ceria-alumina, titania-silica, zirconia-silica, zirconia-titania, ceria-zirconia, and alumina-magnesium oxide.
[0154] The refractory oxide is preferably selected from the group consisting of alumina, silica, ceria, silica-alumina, ceria-alumina, ceria-zirconia and alumina-magnesium oxide. More preferably, the refractory oxide is selected from the group consisting of alumina, ceria, silica-alumina and ceria-zirconia. The refractory oxide can be alumina or silica-alumina.
[0155] It may be preferred that the capture material is free of Pt alloying material (PAM), especially when the Pt alloying material comprises palladium. This embodiment is referred to herein as the "PAM-free embodiment." More preferably, the capture material is free of palladium and platinum. It is further preferred that the capture material is free of one or more platinum group metals (PGMs) and / or one or more coinage metals gold (Au) and / or silver (Ag). Even more preferably, the capture material is free of one or more transition metals (i.e., excluding transition metals that may be part of a refractory oxide such as zirconia). In such circumstances, it is preferred that the capture material is free of Pt alloying material (PAM) and / or PAM-free. 2 Particles of a refractory oxide having an average specific surface area of 1000 nm to 1000 nm / g may be used primarily or solely as the capture material.
[0156] In embodiments that do not include PAM, the refractory oxide is preferably ceria, ceria-alumina, or ceria-zirconia. More preferably, the refractory oxide comprises or consists essentially of ceria. Even more preferably, the refractory oxide consists essentially of ceria.
[0157] Additionally or alternatively, the capture material may include or consist essentially of particles of a Pt alloy material, such as palladium (Pd). Embodiments of the invention in which a Pt alloy material is included in the capture material are referred to herein as "PAM-containing embodiments."
[0158] The inclusion of a Pt alloying material (PAM) in the capture material has been found to be advantageous because it can readily form an alloy with volatile Pt. The formation of an alloy (e.g., a Pt-Pd alloy) between the Pt in the capture material and the Pt alloying material effectively captures the volatile Pt due to the stability of the alloy.
[0159] Typically, the Pt alloy material comprises or consists essentially of a metal and / or its oxide. The metal is preferably selected from the group consisting of palladium (Pd); gold (Au); copper (Cu); a mixture of Pd and Au; a mixture of Pd and Cu; a mixture of Au and Cu; a mixture of Pd, Au and Cu; a binary metal alloy of Pd and Au; a binary metal alloy of Au and Cu; and a ternary metal alloy of Pd, Au and Cu. The metal is preferably selected from the group consisting of palladium (Pd), a mixture of Pd and Au, and a binary metal alloy of Pd and Au. More preferably, the metal is palladium (Pd).
[0160] For the avoidance of doubt, Pt alloy material does not contain platinum (eg, when new or unused).
[0161] The particles of the Pt alloy material preferably have an average particle size of about 10 nm or more, such as an average particle size of more than about 10 nm. More preferably, the particles of the Pt alloy material have an average particle size of about 15 nm or more, such as about 20 nm or more, more preferably about 50 nm or more, such as about 75 nm or more.
[0162] Generally, metals that can function as Pt alloy materials are included in oxidation catalysts due to their catalytic activity. The average particle size of such metals (e.g., palladium) in conventional emission control devices is much smaller than 10 nm. Particles of Pt alloy materials for use in the capture material according to the present invention are relatively large. It has surprisingly been found that such large particles of Pt alloy materials are relatively catalytically inactive, yet capable of capturing or scavenging volatile Pt.
[0163] Typically, the Pt alloy material has an average particle size of 10 nm to 1000 microns. Preferably, the Pt alloy material has an average particle size of 15 nm to 100 microns, more preferably 20 nm to 20 microns, especially 50 nm to 5 microns, for example 75 nm to 3 microns.
[0164] The particles of the Pt alloy material typically have a variance of ≦about 10% (e.g., <about 10%), preferably ≦about 7.5%, such as ≦about 5%, more preferably ≦about 2.5%. The variance measurement refers to virgin Pt alloy material particles (i.e., fresh particles that have not been used repeatedly or prolongedly).
[0165] "Average particle size" and "dispersion" as used herein with respect to Pt alloy materials can be determined using conventional methods or as described in WO 2016 / 128720.
[0166] Typically, the capture material is 1g ft -3 From 50g ft -3 , preferably 4g ft -3 From 40g ft -3 , and even more preferably 8g ft -3 from 30g ft -3 has a total loading of Pt alloy material (e.g., metal content of Pt alloy material).
[0167] The Pt alloy material, for example palladium, can be disposed or supported on a substrate (eg, the Pt alloy material is coated directly onto the substrate).
[0168] The Pt alloy material is preferably disposed or supported on a support material (e.g., a particulate support material). The Pt alloy material can be disposed directly on the support material or directly supported on the support material (e.g., there is no intermediate support material between the Pt alloy material and the support material). For example, the Pt alloy material, e.g., palladium, can be dispersed on the surface of the support material and / or impregnated into the support material.
[0169] Typically, the support material comprises or essentially consists of a refractory oxide, such as those defined above. The refractory oxide is preferably selected from the group consisting of alumina, silica, ceria, silica-alumina, ceria-alumina, ceria-zirconia and alumina-magnesium oxide. More preferably, the refractory oxide is selected from the group consisting of alumina, ceria, silica-alumina and ceria-zirconia. Even more preferably, the refractory metal oxide is selected from alumina or silica-alumina, especially silica-alumina.
[0170] The refractory oxide may be of the type described above having a relatively low average specific surface area and having relatively large particles.
[0171] The present invention includes various configurations of capture materials with respect to catalytic materials including (Pt).
[0172] A first configuration relates to an emission control device that includes a solid foam layer for capturing volatile platinum (Pt), and the emission control device may further include a catalytic material comprising platinum (Pt). Typically, the solid foam layer is positioned to contact the exhaust gas after the exhaust gas has contacted or passed through the catalytic material comprising platinum (Pt).
[0173] The second configuration pertains to an exhaust system including a first emissions control device upstream, preferably directly upstream, of a second emissions control device (i.e., the outlet of the first emissions control device is connected, preferably directly connected, to the inlet of the second emissions control device). The first emissions control device includes a catalytic material disposed or supported on a substrate. The second emissions control device includes a solid foam layer for capturing volatile platinum (Pt) disposed or supported on a substrate.
[0174] For the avoidance of doubt, the capture material and the catalyst material have different compositions.
[0175] Generally, the catalytic material comprises platinum (Pt) disposed or supported on a support material (referred to herein as the catalytic material's support material or "CM support material"). The CM support material comprises or consists essentially of a refractory oxide (referred to herein as the catalytic material's refractory oxide). The refractory oxide particles are typically ≧75 m 2 / g, e.g. ≥ 100m 2 / g, preferably ≥ 100m 2 / g average specific surface area.
[0176] The refractory oxide of the CM support material is typically selected from the group consisting of alumina, silica, titania, zirconia, ceria, and mixed or composite oxides thereof, such as mixed or composite oxides of two or more thereof. For example, the refractory oxide may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, silica-alumina, titania-alumina, zirconia-alumina, ceria-alumina, titania-silica, zirconia-silica, zirconia-titania, ceria-zirconia, and alumina-magnesium oxide.
[0177] The catalytic material may include a single platinum group metal (PGM), platinum (eg, the catalytic material includes platinum as the only platinum group metal).
[0178] Alternatively, the catalytic material may include (i) platinum (Pt), and (ii) palladium (Pd) and / or rhodium (Rh).
[0179] When the catalytic material comprises palladium (Pd), the catalytic material typically comprises particles of palladium (Pd) having an average particle size of <10 nm, preferably ≦8 nm.
[0180] When the catalytic material comprises palladium (Pd), the catalytic material typically comprises palladium (Pd) particles having a dispersion of >10%, preferably ≧15% (e.g. 15 to 35%), for example ≧20% (e.g. 20 to 30%).
[0181] In general, when the catalytic region or catalytic material thereof comprises Pt and Pd (and optionally Rh), typically the mass ratio of Pt to Pd is ≧1:1. The catalytic material may comprise Pt and optionally Pd, such that the mass ratio of Pt to Pd is 1:0 to 1:1. When the catalytic material comprises Pt and Pd (and optionally Rh), the mass ratio of Pt to Pd is ≧1.5:1, more preferably ≧2:1 (e.g. ≧3:1), even more preferably ≧4:1, such as ≧10:1. The mass ratio of Pt to Pd is preferably 50:1 to 1:1, more preferably 30:1 to 2:1 (e.g. 25:1 to 4:1), even more preferably 20:1 to 5:1, such as 15:1 to 7.5:1.
[0182] In general, when the catalytic material comprises Pt and Rh (and optionally Pd), typically the mass ratio of Pt to Rh is ≧1:1. The catalytic material may comprise Pt and optionally Rh, such that the mass ratio of Pt to Rh is 1:0 to 1:1. When the catalytic material comprises Pt and Rh (and optionally Pd), the mass ratio of Pt to Rh is ≧1.5:1, more preferably ≧2:1 (e.g. ≧3:1), even more preferably ≧4:1, such as ≧10:1. The mass ratio of Pt to Rh is preferably 50:1 to 1:1, more preferably 30:1 to 2:1 (e.g. 25:1 to 4:1), even more preferably 20:1 to 5:1, such as 15:1 to 7.5:1.
[0183] In a first configuration, a solid foam layer for capturing volatile platinum (Pt) may include or consist essentially of a capture material. (a) may be disposed on or supported on a catalytic material; and / or (b) may be placed directly on the substrate [i.e., the capture material contacts the surface of the substrate]; and / or (c) may be in contact with the catalytic material [i.e., the capture material is adjacent to or abuts the catalytic material].
[0184] A solid foam layer for capturing volatile platinum (Pt) is positioned in contact with the exhaust gas after it has contacted and / or passed through the catalytic material.
[0185] Generally, the solid foam layer region is configured to contact the exhaust gas as it exits the emission control device. The catalytic material may be configured or oriented to contact the exhaust gas prior to the solid foam layer.
[0186] The solid foam layer is preferably disposed or carried at or near the outlet end of the substrate.
[0187] The catalytic material may be disposed or supported upstream of the solid foam layer. Additionally or alternatively, the solid foam layer may overlap the catalytic material. An end or portion of the solid foam layer may be disposed or supported on the catalytic material. The solid foam layer may completely or partially overlap the catalytic material.
[0188] Generally, the loading of the solid foam layer is 0.1-4.0g.in -3 , preferably 0.5 to 2.0 g.in -3 It is.
[0189] In a third emission control device embodiment, the emission control device includes a substrate and a solid foam layer for oxidizing soot (and optionally carbon monoxide and hydrocarbons). The emission control device is a catalyzed soot filter (CSF).
[0190] The solid foam layer preferably has an open cell structure.
[0191] The substrate is preferably a filtering substrate, such as a wall-flow honeycomb monolith substrate (eg, a particulate filter).
[0192] A solid foam layer for oxidizing soot may be disposed or supported over the inlet and / or outlet channels of the filtering substrate. Preferably, the solid foam layer is disposed or supported over at least the inlet channels of the filtering substrate.
[0193] The solid foam layer for oxidizing the soot comprises or consists essentially of a catalytic material as described above.
[0194] Typically, the catalytic material for oxidizing soot comprises or consists essentially of a platinum group metal disposed on a support material.
[0195] The platinum group metal is preferably platinum and / or palladium.
[0196] The support material comprises or consists essentially of a refractory oxide. The refractory oxide may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, and mixed or composite oxides thereof, such as mixed or composite oxides of two or more thereof. For example, the refractory oxide may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, silica-alumina, titania-alumina, zirconia-alumina, ceria-alumina, titania-silica, zirconia-silica, zirconia-titania, ceria-zirconia, and alumina-magnesium oxide.
[0197] The refractory oxide is preferably selected from the group consisting of alumina, silica, ceria, silica-alumina, ceria-alumina, ceria-zirconia and alumina-magnesium oxide. More preferably, the refractory oxide is selected from the group consisting of alumina, ceria, silica-alumina and ceria-zirconia. The refractory oxide can be alumina or silica-alumina.
[0198] In a fourth emission control device embodiment, the emission control device comprises an exhaust oxidizer for oxidizing particulates (and optionally for oxidizing (i) carbon monoxide and hydrocarbons, and (ii) nitrogen oxides (NO x The emission control device includes a substrate and a solid foam layer for reducing particulate matter (e.g., argon, argon gasoline, etc.). The emission control device is a gasoline particulate filter (GPF).
[0199] The solid foam layer preferably has an open cell structure.
[0200] The substrate is typically a filtering substrate, such as a wall-flow honeycomb monolith substrate (e.g., a particulate filter). The substrate can be a cordierite flow-through monolith, a metal flow-through monolith, a cordierite particulate filter, a silicon carbide particulate filter, or an aluminum titanate particulate filter.
[0201] When the substrate is a wall-flow honeycomb monolith substrate, such as a particulate filter, typically the substrate has a porosity of 40 to 70%, preferably 45 to 65%, such as 50 to 65% (e.g. 55 to 65%). Additionally or alternatively, the substrate may have an average pore size of 8 to 45 μm, preferably 10 to 30 μm (e.g. 10 to 25 μm), especially 15 to 25 μm. The average pore size may be determined by mercury porosimetry.
[0202] In a fourth emission control device embodiment, the solid foam layer can be disposed or carried over the inlet and / or outlet channels of the filtering substrate. Preferably, the solid foam layer is disposed or carried over at least the inlet channels of the filtering substrate.
[0203] The solid foam layer for oxidizing the soot comprises or consists essentially of a catalytic material as described above.
[0204] Typically, the catalytic material comprises or consists essentially of a platinum group metal, a support material and an oxygen storage component.
[0205] The platinum group metal is preferably rhodium and / or palladium.
[0206] The support material comprises or consists essentially of a refractory oxide. The refractory oxide may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, and mixed or composite oxides thereof, such as mixed or composite oxides of two or more thereof. For example, the refractory oxide may be selected from the group consisting of alumina, silica, titania, zirconia, ceria, silica-alumina, titania-alumina, zirconia-alumina, ceria-alumina, titania-silica, zirconia-silica, zirconia-titania, ceria-zirconia, and alumina-magnesium oxide.
[0207] Preferably, the refractory oxide is selected from the group consisting of alumina, silica, ceria, silica-alumina, ceria-alumina, ceria-zirconia and alumina-magnesium oxide. More preferably, the refractory oxide is selected from the group consisting of alumina, ceria, silica-alumina and ceria-zirconia. The refractory oxide is alumina or silica-alumina, more preferably, the refractory oxide is alumina.
[0208] The oxygen storage component typically comprises or consists essentially of ceria.
[0209] The internal combustion engine may be a gasoline engine or a diesel engine. It is preferred that the internal combustion engine is a diesel engine, particularly for the first, second and third emission control device embodiments of the present invention. For the fourth emission control device aspect of the present invention, it is preferred that the internal combustion engine is a gasoline engine.
[0210] definition As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to "a particulate material" includes a mixture of two or more particulate materials, and the like.
[0211] The term "mixed oxide" as used herein generally refers to a mixture of single phase oxides, as conventionally known in the art. The term "complex oxide" as used herein generally refers to an oxide composition having two or more phases, as conventionally known in the art.
[0212] The term "about" as used herein in reference to the endpoints of a numerical range includes the exact endpoints of the numerical range specified. Thus, for example, a term defining a parameter up to "about 0.2" includes that parameter up to and including 0.2.
[0213] As used herein with respect to holding a substrate, the term "substantially vertical" refers to an arrangement in which the central axis of the substrate is ±5° from vertical, preferably ±3° from vertical, for example ±0° from vertical (i.e. perfectly vertical within measurement error).
[0214] The term "vacuum" as used herein refers to a pressure below atmospheric pressure. "Vacuum" should not be taken literally as a space completely devoid of matter. The strength of the vacuum applied to the substrate depends on the composition of the liquid used and the type of substrate. The vacuum should be strong enough to clear the cells of the substrate so that no blockage occurs. Such vacuum strengths or reduced pressures are well known in the art.
[0215] As used herein, the phrase "consisting essentially of" limits the scope of an inventive feature to include the specified materials and any other materials or steps (e.g., minor amounts of impurities, etc.) that do not materially affect the basic characteristics of the inventive feature. The phrase "consisting essentially of" encompasses the phrase "consisting of." EXAMPLES
[0216] The invention will now be illustrated by the following non-limiting examples.
[0217] General Procedures and Methods The established coating method is in accordance with the disclosure and teachings of WO 99 / 47260, WO 2011 / 080525 and WO 2014 / 19568.
[0218] Example 1 A gamma-alumina suspension was prepared by mixing the appropriate amount of powder and water. The pH was adjusted to 5.5 with HNO3 and the suspension was stirred until homogeneous. The suspension was milled and d 50 <6 microns.
[0219] To a portion of this suspension, valeric acid (1.6% of the mass of alumina) was added and the pH was adjusted to 4.8 with NH3. Kenwood Chef Classic equipped with a whisk TM Air was introduced into the suspension using a food mixer and stirred at maximum speed for 10 minutes to produce a foam with a volume 5.9 times that of the starting suspension.
[0220] The foams were aged for 3 days (during which no liquid drainage occurred) and observed for drying and coarsening of the cell structure.
[0221] Example 2 Boehmite powder (alumina supplied by Sasol) was added to demineralized water. The suspension was stirred for 3 hours. Cu-exchanged small pore zeolite (3.0 wt.% Cu) with CHA structure and SAR of 25 was slowly added (zeolite:boehmite ratio 9:1). The total solids content of the suspension was 31 wt.%.
[0222] To a portion of this suspension, valeric acid (various amounts as listed in Table 1) was added and the pH was adjusted to 4.8 with NH3. TM Air was introduced into each portion of the suspension using a food mixer and mixed at maximum speed for 10 minutes to generate a foam. TIFF0007603567000001.tif79170
[0223] Figure 1a shows an optical microscopy evaluation of the fresh foam of Sample I (magnification 5x and scale bar 0.20 mm). Figure 1b shows an optical microscopy evaluation of the fresh foam of Sample I (magnification 5x and scale bar 0.25 mm).
[0224] Example 3 - SCR Foam Coating Test A suspension was prepared by diluting a suspension of similar composition to that in Example 2 and then stirring until homogenous.
[0225] To a portion of this suspension, valeric acid (2.1% of the mass of the solid component) was added and the pH was adjusted to 4.8 with tetra-n-propyl-ammonium hydroxide. TM Air was introduced into the suspension using a food mixer and stirred at maximum speed for 10 minutes to generate a foam.
[0226] Using a vacuum applied from the inlet end, the foam was introduced into the outlet end of a 1-inch core taken from a cordierite flow-through substrate. The core was dried and then calcined at 500°C for 2 hours.
[0227] Scanning electron microscopy of the coated cores showed that the solid foam coating formed a uniform layer on the cell walls, as shown in Figure 2. Open air bubbles are visible at the surface of the solid foam layer. Images were taken under the following conditions: 2a) accelerating voltage 20 kV, magnification 42x, working distance 18 mm, secondary electron detector, scale bar 0.20 mm, 2b) accelerating voltage 20 kV, magnification 28x, working distance 13 mm, secondary electron detector, scale bar 0.20 mm.
[0228] Example 4 - SCRF Foam Coating Testing Three suspensions were prepared, one each as in Examples 2 and 3. To each of these, valeric acid (in the amount listed in Table 2) was added and the pH was adjusted to a target of 4.75 with tetra-n-propyl-ammonium hydroxide (TPAOH). TMAir was introduced into the suspension using a food mixer and stirred at maximum speed for 10 minutes to generate a foam. TIFF0007603567000002.tif74170
[0229] Example 4a Using the method described in WO 2011 / 080525, 196.6 g of suspension 4a was applied to the outlet channel of a SiC filter substrate having 300 cells per square inch. The foam coating was dried using forced air flow and baked at 500° C. The coated substrate was sectioned longitudinally to examine the coating depth and the coating was examined using SEM.
[0230] FIG. 3 shows the coating of suspension 4a on one segment of the substrate after cutting it longitudinally.
[0231] The depth of the foam coating was 38 mm as measured from the outlet side. The catalyst was 1.2 g.in -3 The coating had a coating loading of 100 nm. The distribution of the coating on the channels appears to be homogenous. The coating surface is very rough. The bubble-like features have a size distribution ranging from 50 μm to 200 μm and appear to be frequently interconnected by either cracks or holes in the bubble walls. Figure 4 shows images of the coated filter, 4a showing the coating surface and 4b showing a cross-section. The images were taken under the following conditions: 4a) accelerating voltage 20 kV, magnification 45x, working distance 14 mm, secondary electron detector, scale bar 0.10 mm, 4b) accelerating voltage 20 kV, magnification 200x, working distance 13 mm, secondary electron detector, scale bar 0.10 mm.
[0232] Cross sections show that the coating forms a dense, thin walled layer above which a coarser open structure forms. The coating does not penetrate into the substrate pores. Both the inlet and outlet channel intra-wall pores are uncoated. The thickness of the dense walled layer is variable and the degree of open porous structure formed above it also varies from sample to sample. The dense layer shows interparticle porosity in the range of 1-5 μm.
[0233] Example 4b The two-part suspension 4a was applied to the outlet channels of a SiC filter substrate having 300 cells per square inch using the method described in WO 2011 / 080525. The first application was 223.3 g of foam and the second application was 143.0 g of foam. The foam coating was dried using a forced air stream after each application and baked at 500° C. The coating was examined using SEM.
[0234] Figure 5 shows images of the coated filter, 5b shows the coating surface, and 5a and 5c show cross-sections. The images were taken under the following conditions: 5a) accelerating voltage 20 kV, magnification 88x, working distance 16 mm, secondary electron detector, scale bar 0.20 mm, 5b) accelerating voltage 20 kV, magnification 81x, working distance 18 mm, secondary electron detector, scale bar 0.10 mm, 5c) accelerating voltage 20 kV, magnification 150x, working distance 13 mm, secondary electron detector, scale bar 0.10 mm.
[0235] The coating forms a thick homogeneous layer on the substrate walls. The thickness next to the corners is about 350 μm and along the walls is about 150 μm. The coating forms a very rough surface and has open porosity interconnected by cracks or holes in the cell walls. Much smaller pores are found between the particles that form the cell walls.
[0236] Example 4c Using the method described in WO 2011 / 080525, three parts of Suspension 4c were applied to the outlet channels of a SiC filter substrate having 300 cells per square inch. The first application was 191.1 g of foam, the second application was 170.8 g of foam, and the third application was 193.6 g of foam. The foam coating was dried using a forced air stream after each application and baked at 500° C. The coatings were examined using SEM.
[0237] Figure 6 shows images of the coated filter, 6a showing the coating surface and 6b showing a cross-section. The images were taken under the following conditions: 6a) accelerating voltage 20 kV, magnification 90x, working distance 14 mm, secondary electron detector, scale bar 0.10 mm, 5b) accelerating voltage 20 kV, magnification 80x, working distance 12 mm, secondary electron detector, scale bar 0.10 mm.
[0238] The coating appears homogeneous; the coating surface is very rough. The bubble-like features have a wide size distribution ranging from 50 μm to 250 μm, and appear to be frequently interconnected by either cracks or holes in the bubble walls. The overall thickness of the layer around the corners is 300 μm, and over the channels is approximately 160 μm.
[0239] The cross sections show that the coating forms a dense layer on the walls, above which a coarser open structure forms. The average thickness of the bottom dense layer varies greatly along the channel, from 20 to 150 μm, depending on the presence and number of bubbles in the region.
[0240] Example 5 - Short Coating Depth Test Example 5a - Filter ASC Stripes Prior to application of the foam coating layer, the filter was coated with a conventional SCR washcoat layer for filters.
[0241] A suspension is prepared by adding gamma-alumina powder to water to obtain a d of less than 4.5 microns. 50The mixture was ground to a fine powder. A soluble salt of Pt and 0.5% hydroxyethylcellulose were added. The suspension was stirred to homogenize.
[0242] To a portion of this suspension, propyl gallate (2.2% of the mass of the solid components) was added and stirred until homogeneous. TM Air was introduced into the suspension using a food mixer and stirred at maximum speed for 10 minutes to generate a foam.
[0243] The foam was applied to the outlet channels of a SiC filter substrate having 300 cells per square inch using the method described in WO 2011 / 080525. The foam coating was dried using forced air flow and baked at 500°C. The depth of the foam coating was 5 mm, measured from the outlet side. The resulting catalyst had a mass of 14 g.ft of solid foam in the coated area. -3 Pt loading of 0.4g.in -3 had a coating loading of 1000 mg / g.
[0244] The catalyst was cut longitudinally in two perpendicular planes, and by viewing the surface of the solid foam layer using an optical microscope, it could be determined that the solid foam had an open-cell structure with cells between 5 and 140 μm, as shown in FIG.
[0245] The coating depth of the solid foam layer was measured at 10 equally spaced locations across the two cut surfaces, with an average coating depth of 4.8 mm and a standard deviation of 0.4 mm.
[0246] Example 5b - Flow-through ASC stripes A suspension was prepared by adding gamma-alumina powder (SCFa-140, supplied by Sasol) to water to obtain a d of 4.5 microns. 50 The mixture was ground to a fine powder. A soluble salt of Pt and 0.5% hydroxyethylcellulose were added. The suspension was stirred to homogenize.
[0247] To a portion of this suspension, valeric acid (1.65% by mass of solid content) was added and the pH was adjusted to 4.8 with NH3. Kenwood Chef Classic equipped with a whisk TM Air was introduced into the suspension using a food mixer and stirred at maximum speed for 10 minutes to generate a foam.
[0248] The foam was applied to the outlet channels of a cordierite flow-through substrate having 300 cells per square inch using the method described in WO 2011 / 080525. The foam coating was dried using forced air flow and calcined at 500°C. The depth of the foam coating was 16.1 mm as measured from the outlet side. The resulting catalyst weighed 60 g.ft on the coated portion. -3 Pt loading of 1.4g.in -3 had a coating loading of 1000 mg / g.
[0249] The catalyst was cut longitudinally in two perpendicular planes, and when the surface of the solid foam layer was viewed using an optical microscope, it could be determined that the solid foam had an open-cell structure with cells between 20 and 250 μm, as shown in FIG.
[0250] The coating depth of the solid foam layer was measured at 10 equally spaced locations across the two cut surfaces, with a mean coating depth of 15.7 mm and a standard deviation of 0.7 mm.
[0251] A wide variety of doses were applied to the flow-through substrate to achieve different short coating depths, as shown in Table 3 below. TIFF0007603567000003.tif72170
[0252] Example 6: DOC Coating (Non-foamed) Silica-alumina powder was slurried in water, 90Grind to <20 microns. Barium acetate was added to the slurry followed by appropriate amounts of soluble platinum and palladium salts. Beta zeolite was added such that the slurry contained 77% silica-alumina and 23% zeolite by mass. The slurry was stirred to homogenize. The resulting washcoat was applied to the inlet channels of a flow-through monolith using established coating techniques such as those described in WO 99 / 47260. It was then dried and calcined at 500°C.
[0253] A second slurry of silica-alumina powder in water was added to the 90 The slurry was crushed to <20 microns. A soluble platinum salt was added followed by manganese nitrate. The mixture was stirred to homogenize. The slurry was applied to the outlet end of a cordierite flow-through monolith using established coating techniques such as those described in WO 99 / 47260. This was then dried and calcined at 500°C. The manganese loading of the part was 50g ft -3 The finished catalyst was 112.5 g ft -3 Pt loading of 37.5g ft -3 and had a Pd loading of .
[0254] Example 7: Pt Volatile Capture Zone (Foam) Specific surface area (SSA) m containing 1.2 wt% Pd 2 / g of preformed Pd on alpha alumina was slurried in water and 90 The suspension was milled to <20 microns. Activated boehmite slurry was added as a binder (as 10% of the total solids content) and water was added until the suspension had a total solids content of 25%. 0.6% by weight of a cellulose-based thickener was added to the suspension. The pH of the suspension was then adjusted to 4.7 by adding aqueous ammonia and valeric acid (0.2%). Air was introduced into the suspension using a gas-inducing impeller for 15 minutes to generate a stable foam.
[0255] Foam was then dosed onto the outlet face of a round, 143.8 mm diameter, 97 mm long flow-through monolith using established coating techniques as described in WO 2011 / 080525, resulting in a coating depth of 8 mm. The part was dried and calcined at 500 °C. Figure 12 shows an X-ray image of the coated monolith of Example 7, which includes the DOC coating of Example 6 with a foamed Pt volatile coating. In this figure, the outlet is at the top of the image, and a short (6-10 mm) foam coating is visible as a dark band directly over the outlet.
[0256] In some embodiments, by applying similar techniques, the coating depth is between 6 and 10 mm.
[0257] Pt volatile smoke furnace Testing was carried out in a first synthetic catalyst activity test (SCAT) experimental reactor as illustrated in FIG. 9, where an aged core of coated Cu / CHA zeolite SCR catalyst was placed in a conduit downstream of the core of either Example 6 or 7. The syngas mixture was passed through the conduit at a rate of 6 liters / min. A furnace was used to heat (or "age") the DOC sample at steady state temperature for 2 hours at a catalyst outlet temperature of 900°C. The SCR catalyst was placed downstream of the DOC sample and maintained at a catalyst temperature of 300°C during the aging process by adjusting the length of the tube between the furnace outlet and the SCR inlet, although a water-cooled heat exchanger jacket could be used if desired. Temperature was determined using appropriately positioned thermocouples (T1 and T2). The gas mixture used during aging was 40% air, 50% N2, 10% H2O.
[0258] Performance Results-SCR NO x test The SCR core was tested for NOx conversion activity using a syngas bench reactor. The tests were performed with a syngas mixture (maximum available NO xFor a conversion of 65%, use O2 = 10%; H2O = 5%; CO2 = 7.5%; NH3 = 325 ppm; NO = 500 ppm; NO2 = 0 ppm; N2 = remainder, i.e., use an alpha value of 0.65 (NH3:NO x The NO x The transformation is shown in FIG.
[0259] For the avoidance of doubt, the entire contents of all references cited herein are hereby incorporated by reference.
Claims
1. 1. An emission control device for treating or removing pollutants from exhaust gases produced by an internal combustion engine, comprising a solid foam layer disposed on a substrate, the solid foam layer disposed on the substrate comprising a particulate material that is a catalyst material comprising a catalytically active metal uniformly supported on a support material and having an open-cell structure.
2. 10. The emission control device of claim 1, wherein the solid foam layer has a cell volume, and more than 20% of the cell volume are interconnected.
3. 3. The emission control device of claim 1 or 2, wherein the solid foam layer has a median pore diameter of 1 to 100 μm.
4. 4. The emission control device of any one of claims 1 to 3, wherein the solid foam layer comprises cell-like structures having a size distribution in the range of 5 μm to 500 μm.
5. The emission control device of claim 1 , wherein the solid foam layer comprises a partially collapsed structure.
6. 6. The emission control device of claim 1, wherein the solid foam layer has a thickness of 500 μm or less.
7. The emission control device of claim 1 , wherein the solid foam layer is substantially located on the channel walls.
8. The emission control device of claim 1 , wherein the substrate is a porous monolith.
9. 9. The emission control device of claim 1, wherein the catalytically active metal is at least one transition metal selected from iron, copper, nickel, gold, platinum, palladium, rhodium and ruthenium.
10. 10. The emission control device of any one of claims 1 to 9, wherein the support material is a refractory oxide, a metal aluminate, or a zeolite.
11. 11. An emission control device according to any one of claims 1 to 10, wherein the support material is a refractory oxide selected from the group consisting of alumina, silica, titania, magnesia, zirconia, ceria, lanthana and mixed or composite oxides of two or more thereof, such as silica-alumina, titania-alumina, zirconia-alumina, ceria-alumina, titania-silica, zirconia-silica, zirconia-titania, ceria-zirconia, ceria-zirconia-alumina or alumina-magnesium oxide.
12. 12. The emission control device of any one of claims 1 to 11, wherein the particulate material is a metal oxide based SCR catalyst formulation, a molecular sieve based SCR catalyst formulation, or a mixture thereof.
13. 13. The emission control device of claim 12, wherein the particulate material is a molecular sieve based SCR catalyst formulation, preferably the molecular sieve based SCR catalyst formulation comprises a transition metal exchanged molecular sieve.
14. 14. The emission control device of claim 13, wherein the transition metal of the transition metal exchanged molecular sieve is copper and the molecular sieve is a zeolite having a framework structure represented by the framework type code CHA.
15. 15. Use of an emission control device according to any one of claims 12 to 14 in an exhaust system of an internal combustion engine to avoid the build-up of back pressure in the exhaust system.
Citation Information
Patent Citations
Catalyst for purifying exhaust gas
JP2002253968A
